Drainage, irrigation and fibrinolytic therapy (DRIFT) for posthaemorrhagic ventricular dilatation: 10-year follow-up of a randomised controlled trial. Issue 5 (4th July 2020) - Luyt, Karen; Jary, Sally L; Lea, Charlotte L; Young, Grace J.; Odd, David E; Miller, Helen E; Kmita, Grazyna; Williams, Cathy; Blair, Peter S; Hollingworth, William; Morgan, Michelle; Smith-Collins, Adam P; et al.
Abstract : Background: Progressive ventricular dilatation after intraventricular haemorrhage (IVH) in preterm infants has a very high risk of severe disability and death. Drainage, irrigation and fibrinolytic therapy (DRIFT), in a randomised controlled trial (RCT), reduced severe cognitive impairment at 2 years. Objective: To assess if the cognitive advantage of DRIFT seen at 2 years persisted until school age. Participants: The RCT conducted in four centres recruited 77 preterm infants with IVH and progressive ventricular enlargement over specified measurements. Follow-up was at 10 years of age. Intervention: Intraventricular injection of a fibrinolytic followed by continuous lavage, until the drainage was clear, and standard care consisting of control of expansion by lumbar punctures and if expansion persisted via a ventricular access device. Primary outcome: Cognitive quotient (CQ), derived from the British Ability Scales and Bayley III Scales, and survival without severe cognitive disability. Results: Of the 77 children randomised, 12 died, 2 could not be traced, 10 did not respond and 1 declined at 10-year follow-up. 28 in the DRIFT group and 24 in the standard treatment group were assessed by examiners blinded to the intervention. The mean CQ score was 69.3 (SD=30.1) in the DRIFT group and 53.7 (SD=35.7) in the standard treatment group (unadjusted p=0.1; adjusted p=0.01, after adjustment for the prespecified variables sex, birth weight and IVH grade). Survival without severe cognitive disability was 66% in the DRIFT group and 35% in the standard treatment group (unadjusted p=0.019; adjusted p=0.003). Conclusion: DRIFT is the first intervention for posthaemorrhagic ventricular dilatation to objectively demonstrate sustained cognitive improvement. Trial registration number: ISRCTN80286058 .